2018
DOI: 10.1016/j.joei.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The performance of nickel-loaded lignite residue for steam reforming of toluene as the model compound of biomass gasification tar

Abstract: , C. (2017). The performance of nickel-loaded lignite residue for steam reforming of toluene as the model compound of biomass gasification tar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…On account of the fact that the WGS reaction (Equation ) is an exothermic reaction, the increase of temperature promotes the reaction to the direction of CO production, thus resulting in the reduction of the concentration of CO 2 and H 2 . The same results are obtained from Xiao et al, who evaluated toluene steam reforming on nickel‐loaded lignite residue catalysts, and observed that H 2 concentration and carbon conversion were enhanced with the temperature from 850 to 900 K, while the temperature rose to 950 K the conversion and H 2 concentration decreased.…”
Section: Resultssupporting
confidence: 83%
“…On account of the fact that the WGS reaction (Equation ) is an exothermic reaction, the increase of temperature promotes the reaction to the direction of CO production, thus resulting in the reduction of the concentration of CO 2 and H 2 . The same results are obtained from Xiao et al, who evaluated toluene steam reforming on nickel‐loaded lignite residue catalysts, and observed that H 2 concentration and carbon conversion were enhanced with the temperature from 850 to 900 K, while the temperature rose to 950 K the conversion and H 2 concentration decreased.…”
Section: Resultssupporting
confidence: 83%
“…On the other hand, the toluene conversation was decreased then the major process was the gasification of catalyst instead of the reforming of toluene. 46 Therefore, the rise in the gas yield also can be arisen from the consumption of AC in Equations (5) and (6).…”
Section: Co + H 2 O = Co 2 + H 2 : ð4þmentioning
confidence: 99%
“…As shown in Figure 1, uncontrollable energy loss is caused by external factors that are difficult to improve, such as coal quality and ambient temperature. Currently, as a result of coal diversity, many power plants choose to conduct coal blending [16] and raw coal separation processes [17] before burning, to reduce the energy loss caused by changes in coal quality. Controllable energy loss can be divided into operational loss and maintenance loss.…”
Section: Analysis Of Energy Loss Of Thermal Generatorsmentioning
confidence: 99%